Structure and evolution of the SW Barents Sea basin province - Boukili, Mourad (2006)
The Barents Sea has experienced several different tectonic phases where three major post-Caledonian rifting periods can be identified, namely Late Devonian Carboniferous, Middle Jurassic Early Cretaceous, and Early Tertiary. Petroleum systems in the SW Barents Sea were developed and greatly affected during these rift stages. Of particular interest in the regional hydrocarbon evolution is the Cenozoic exhumation of the Barents Sea, an event which is poorly understood and widely debated. However, it is commonly agreed that uplift and erosion occurred during late Cenozoic played a major role in source rock maturation, and hydrocarbon migration and accumulation in the SW Barents Sea. The objective of the thesis is to establish the basin evolution of the SW Barents Sea with special focus on the Hammerfest Basin which represents a major hydrocarbon province, and to evaluate the effects of that evolution on the established petroleum systems. The study is carried out through an integrated analysis of seismic reflection profiles and gravity modeling and provides an updated insight on the shallow and deep structures of the study area. In order to better constrain the geological evolution of the region and to identify its effects on the developed petroleum systems an interactive basin modeling approach was used. In the performed basin modeling, well-constrained parameters are utilized and tested to trace the different changes that occurred in the petroleum systems (e.g. subsidence, temperature, maturation) during the basin evolution